A corpus-based research on linguistic expressions denoting politeness in american and british political speeches - Tôn,Nữ Hoàng Yến. (2016)
First of all, I would like to express my sincerest gratitude to my supervisor Dr. Tran Huu Phuc for introducing me into the exciting field of linguistic politeness under the umbrella of corpus-based methodology which I had little knowledge of before. I would also like to express gratitude to my supervisor for his patient guidance, as well as his practical and targeted advices. These are the factors which have contributed to the production of a better version of the study. I would like to show my profound gratitude to all the lecturers in University of Foreign Language Studies, the University of Danang for tirelessly devoting time and efforts to enrich, broaden and deepen my knowledge over the past two years. I am deeply indebted to my whole family, my mother, my brothers and my sister, especially my husband and my little daughters. Indeed, I can hardly find words to describe the strong and immense support they offered during my years of study. Finally, I can not fully express my gratitude to all people who directly and indirectly offer suggestions for improvement and support me to accomplish my thesis in time.